Capital social y asociatividad en el cantón Salcedo - Osorio Castellano, Thalía Aracely (2022)
The actual research had as aim to determine the relationship between Social Capital and the Popular and Solidarity Economy (EPS) active organizations number from Salcedo canton. For this study, was performed research with a quantitative approach, that is, based on the data collection and analysis, whose design was a correlational type, since for proposed aim achievement, were measured and assessed the variables and the statistical relationship the variables, between themselves. Thus, it was also used as a instrument a survey, which is incorporated sociodemographic variables, what can explain the social capital behavior, the relationships quality and quantity and participation into labor associations, and the elements that have an social capital impact to reach their respective analysis. This instrument was divided by sections, which covered general information and the social capital dimensions that were validated and applied to a representative sample from Salcedo canton. It is important to emphasize, what this analysis helped to identify statistically significant variables within social capital or its alternate measurement forms within the Salcedo canton. The most outstanding results allowed identifying that the best assessed dimension was information and communication, as well as identifying, which the dimension is found below the average is cooperation. Therefore, it is not achieved to get a good associative performance and meet the set aims by the associations, making evident an average social capital for 3.17 Salcedo canton. Regarding the EPS activity rate in the Canton is kept 57.44% remain active. From these results were identified a possible relationship between social capital and the activity rate, at finding that said relationship, through the Pearson coefficient is low, therefore, it would be advisable to study the associative and functional performance to identify some possible determining factors.